Formulasi Tablet Kunyah Asetosal Dengan Variasi Konsentrasi PVP Sebagai Bahan Pengikat - Nurul Hidayati; Ninda Meilany; Sholikhah Deti Andasari (CERATA Jurnal Ilmu Farmasi, 2020)
Acetosal which at low doses can be efficacius as an antiplatelet. Acetosal chewable tablet thereby increasing compliance in taking the drug. The aim of this study was to know the effect of polivini pirolidone (PVP) concentration to physical properties and to find out the concentration of PVP which produces the best physical properties. Acetosal chewable tablet is made by direct compression method into 3 formulas with variations concentrations of PVP binder, the first (FI) is using PVP 1%, the second (FII) PVP 3%, the thirth (FIII) PVP 5%. The tablet evaluation included weight uniformity, hardness, friability, disintegration time, liking and responsiveness. The homogeneous analysis used the one-way ANOVA method and the post hoc LSD test, then if the data were not homogeneous, the Kruskall-Wallis test and the Mann-Whitney test. The results showed that the variation in the concentration of PVP as a binder had an effect on the physical properties of acetosal chewable tablets, namely the increase in PVP could increase the brittleness of the tablets, reduce the hardness and disintegration time of the tablets. The PVP 3% concentration in formula II produced the best physical properties of acetosal chewable tablets, namely fulfilling the requirements for weight uniformity, hardness 4,549 ± 0,306 kg, friability 0,183 ± 0,076 %, disintegration time 14,20 ± 0,255 minutes and can be accepted by consumers in the preference and taste response test.